Feasibility and acceptability of remote administration of the cold pressor test - Salwen-Deremer, Jessica K.; Horrigan, Jamie M.; Westvold, Sarah J.; Haythornthwaite, Jennifer A. (Frontiers in Pain Research, 2024)
ObjectiveQuantitative sensory testing is often used to investigate pain in the context of experimental and clinical research studies. However, many of the devices used for QST protocols are only available in resource rich environments, thereby inadvertently limiting the possible pool of participants. Development of remote protocols for appropriate QST measures has the potential to reduce barriers to participation in research.MethodsParticipants with insomnia and Crohn's disease were recruited as part of a clinical trial. We adapted a remote version of the cold pressor test for use during telehealth-based study assessments. Herein, we present data from the baseline assessments including an assessment of feasibility and acceptability of the task.Results100% of participants (N = 28) were able to complete the remote cold pressor test using a combination of materials from their homes and mailed by the study team. Temperature changes during the test were minimal and fairly evenly balanced between increases and decreases. Correlations between submersion time and both general and disease specific pain trended toward significance.ConclusionsWe demonstrated that a remote version of the cold pressor test is feasible and acceptable in a clinical population and provided a step-by-step protocol for administration to facilitate use in other studies.